Making Ointment Of Burn Extract Etanol 96% Binahong Leaf ( Anredera Cordifolia ( Ten.) Steenis) With Method Of Maserasi - Budianto, Teguh; Parmadi, Anom (IJMS - Indonesian Journal on Medical Science, 2014)
ABSTRACT: Background : Anredera cordifolia (Ten.) Steenis, better known under the name binahong leaf, a plant belonging to the family Basellaceae form that contains saponins, alkaloids, polyphenols. This plant in the community are more often used as a cure bruises, scars drugs and drug burns.Objective : In order for use in the treatment of more practical then binahong leaf extract made in the preparation of ointments used as a burn treatment. Ointment has several advantages such as protection to prevent contact with the skin surface of the skin stimulation, stable in use and storage, easy to use, easily distributed evenly so that a healing effect immediately.Methods : This research was pre-experimental quantitative research which used experimental in laboratory. The sampling technique that was used is random sampling. The analyze test used t test independent sample.Result : maceration yield = 1.08% w/w, organoleptic of greenish-black ointment preparation to smell the scent of jasmine, 6 near-normal pH test, homogeneity test = there was homogeny ointment, 5.43 seconds adhesion test, test power proteksions 5 minutes to provide protection on base effect, dispersive power test using 7.06 cm2 glass, with a load of 50 g glass=9.95 cm2, with a glass + load 100=12.56 g cm2.Conclussion : There was Binahong ointment have several advantages such as protection to prevent contact with the skin surface of the skin stimulation, stable in use and storage, easy to use so that a healing effect immediately..Keywords: binahong ointment,drug burns, Anredera cordifolia (Ten.)